Avaliação da presença de resistência transmitida e/ou polimorfismos aos antirretrovirais raltegravir, darunavir e etravirina, em indivíduos infectados pelo vírus da imunodeficiência humana tipo 1 (HIV-1) agrupados de acordo com o tempo de infecção - Arnold, Rafael [UNIFESP] (2017)
ABSTRACT Infections caused by the HIV have reached alarming levels all over the world, being Brazil the most affected country in Latin America. High recombination rate of the viral genome, associated with the high frequency of polymorphisms, selective pressure caused by antiretrovirals, and the transmission of strains resistant to drugs put in check the efficacy of the treatment, especially when considering the late presenters, once the degradation of the immune system and consequently a decrease in life quality and expectation are seen. This study evaluated and differentiated the transmitted resistance and polymorphisms towards the antiretrovirals Raltegravir, Darunavir and Etravirine in individuals with late diagnosis (n= 17) versus recent infection (n=22) by HIV-1. Integrase, protease and reverse transcriptase were amplified via nested-PCR and sequenced through Next Generation Sequencing using the MiSeq, Illumina platform. Mutations and polymorphisms with a frequency lower than 1% were excluded from the analysis. Clinical data of the late presenters showed that the damage caused in the immune system led these individuals to develop AIDS defining comorbities as well as presenting low levels of TCD4+ lymphocytes, although presenting immune reconstitution above 30% since an adequate drug combination was used, the levels of TCD4+ lymphocytes remained low, compromising the treatment as well as the prognostic. In this group, two mutations for Etravirine were found (V106I and E138Q) one for Raltegravir (T97A) and none for Darunavir. In the recently infected individuals, no resistance mutation for Darunavir or Raltegravir was found, but for Etravirine the accessory mutation A98G was found in two individuals, as well as the major mutations K101P and V179E in three and two individuals respectively. K103N was found in both groups and in several individuals, which may lead to a negative impact on the treatment. The difference in the viral diversity found when both groups were compared was not statistically significant. More attention should be given to the protease inhibitors, which in both groups were significantly present. A better use of the large amount of data generated is possible, under the suggestion of using the multiplex technique through DNA barcoding, reducing the time spend in the development of the procedures, as well as the financial expenses.